Induksi Tunas Tanaman Rasberi Hitam (Rubus occidentalis L.) Melalui Direct Organogenesis Secara In Vitro - SUGIARI, LUH PUTU; SRITAMIN, MADE; DWIYANI, RINDANG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Induction of Black Raspberry Buds ( Rubus occidentalis L. ) Through Direct Organogenesis In Vitro. Supervised Black Raspberry plants are sources of various bioactive compounds such as phenolic compounds or phenolic acids, flavonoids, anthocyanins, flavonols, and tannins that are used as medicine. Black Raspberry also have a wide market share, the price reaches Rp 200,000 per kg. Propagation of black raspberry in a conventional way requires a long time. This study aims to obtain black raspberry seedlings in a relatively short time and large quantities through direct organogenesis in vitro. This research was divided into two, namely research on the sterilization method and the effect of gowth regulators with six treatments. The data were analyzed descriptively. The results of this study indicated that sterilization using tween 20 and vitamin C could reduce the occurrence of contamination and browning in explants respectively by 33.3% and 100%. The used of MS media + 2 ppm BAP + 150 ml coconut water + 0.01 ppm NAA (K4) treatment showed a response of gowth of shoots and leaves on the plantlet of 100%.